Petrography and geochemical framework of guébaké dolerites dyke swarms (north Cameroon, central Africa) - Togo, Abondou; Oumarou Faarouk, Nkouandou; Tefogoum Ghislain, Zangmo; Mefire Aminatou, Fagny; Dawai, Daouda; Appoliaire, Dinamou; Dagwai Justin, Guihdama; Haman, Adama (International Journal of Advanced Geosciences, 2022)
Dolerites dykes of 4.5 to 25 m wide extend from 200m to 1km, crosscut the Guébaké granitoids basement in northern Cameroon along EW to N100E directions. Petrographic studies reveal the microlitic porphyritic texture to classical doleritic texture of ophitic to sub-ophitic types. Guébaké dolerites are mainly composed in various proportions of skeletal plagioclase and feldspar, clinopyxene, amphibole and oxides crystals. ICP-MS and ICP-AES geochemical analyses have distiguished a lava series composed of trachybasalts, basaltic trachyandesites, trachyandesites, trachytes and rhyolites of continentale tholeiites affinity. Lavas have been differenciated trough fractional crystallization process coupled with crustal contamination and metasomatism. Guébaké dolerites are products of relatively high partial melting rate of E-MORB mantle component. They stand as fingerprints of the post pan African crustal consolidation and precursor of the development of central African rift system at Cretaceous times.